Welcome to OStack Knowledge Sharing Community for programmer and developer-Open, Learning and Share
Welcome To Ask or Share your Answers For Others

Categories

0 votes
519 views
in Technique[技术] by (71.8m points)

recursion - How to recursively reverse a list using only basic operations?

I was wondering how to reverse a list using only basic operations such as cons, first, rest, empty?, etc.

No helper functions or accumulators allowed, and the function only takes one input - a list.

I was told it was possible, though I can't wrap my head around it.

This is what I have conceptualized so far. I don't know how to form the recursion for the rest of the list.

(defunc rev-list (x)
  (if (or (equal (len x) 0) (equal (len x) 1))
      x
      (cons (first (rev-list (rest x)))
            ???)))

Apparently it is possible to do something similar with a function that swaps the first and last of a list, though I don't fully understand it either. Here is the code for it:

(define swap-ends (x)
  (if (or (equal (len x) 0) (equal (len x) 1))
      x
      (cons (first (swap-ends (rest x))) 
            (swap-ends (cons (first x) 
                             (rest (swap-ends (rest x))))))))
See Question&Answers more detail:os

与恶龙缠斗过久,自身亦成为恶龙;凝视深渊过久,深渊将回以凝视…
Welcome To Ask or Share your Answers For Others

1 Answer

0 votes
by (71.8m points)

(note: the answer is at the bottom of this post) The 2nd function,

(define (swap-ends x)                                   ; swap [] = []
  (if (or (equal (length x) 0) (equal (length x) 1))    ; swap [x] = [x]
      x                                                 ; swap (x:xs) 
      (cons (first (swap-ends (rest x)))                ;    | (a:b) <- swap xs 
            (swap-ends (cons (first x)                  ;    = a : swap (x : b)
                             (rest (swap-ends (rest x))))))))

(with Haskell translation in the comments) what does it do, you ask? The data flow diagram for if's alternative clause is

                   /-> first ----------------------> cons
x --> first ------/-------------> cons --> swap --/
  -> rest -> swap ---> rest ---/

(follow the arrows from left to right). So,

[] -> []
[1] -> [1]
                     /-> 2 -----------------------> [2,1]
[1,2] --> 1 --------/------------> [1] --> [1] --/
      -> [2] -> [2] ---> [] ---/

                           /-> 3 -------------------------> [3,2,1]
[1,2,3] --> 1 ------------/----------> [1,2] --> [2,1] --/
        -> [2,3] -> [3,2] -> [2] --/

                             /-----> 4 ----------------------------> [4,2,3,1]
[1,2,3,4] --> 1 ------------/---------------> [1,3,2] -> [2,3,1] -/
          -> [2,3,4] -> [4,3,2] -> [3,2] -/

So far it indeed does swap the end elements of a list. Let's prove it by the natural induction,

true(N-1) => true(N):

                       /-> N --------------------------------------> [N,2..N-1,1]
[1..N] --> 1 ---------/-----------> [1,3..N-1,2] -> [2,3..N-1,1] -/
       -> [2..N] -> [N,3..N-1,2]   /
                    -> [3..N-1,2] -/

So it is proven. Thus, we need to devise a data flow diagram which, under the supposition of reversing an (N-1)-length list, will reverse an N-length list:

[1..N] --> 1 ------------------------------------
       -> [2..N] -> [N,N-1..2] -> N -------------------------------
                     -> [N-1,N-2..2] -> [2..N-1] -> [1..N-1] -> rev -> cons

Which gives us the implementation

(define (rev ls)                                 ; rev [] = []
  (cond                                          ; rev [x] = [x]
    ((null? ls) ls)                              ; rev (x:xs) 
    ((null? (rest ls)) ls)                       ;   | (a:b) <- rev xs 
    (else                                        ;   = a : rev (x : rev b)
      (cons (first (rev (rest ls)))
            (rev (cons (first ls)
                       (rev (rest (rev (rest ls))))))))))

(rev '(1 2 3 4 5))     ; testing
;Value 13: (5 4 3 2 1)

The Haskell translation in the comments follows the diagram quite naturally. It is actually readable: a is the last element, b is the reversed "core" (i.e. the input list without its first and last element), so we reverse the reversed core, prepend the first element to get the butlast part of the input list, then reverse it and prepend the last element. Simple. :)

2020 update: here's a Scheme version based on the code by @R?rd from the comments, such that it is similarly readable, with arguments destructuring in place of Haskell's pattern matching:

(define (bind lst fun)
  (apply fun lst))

(define (rev lst)
  (if (or (null? lst)
          (null? (cdr lst)))
    lst
    (bind lst
      (lambda (first . rest)
         (bind (rev rest)
           (lambda (last . revd-core)
              (cons last (rev (cons first (rev revd-core))))))))))

与恶龙缠斗过久,自身亦成为恶龙;凝视深渊过久,深渊将回以凝视…
Welcome to OStack Knowledge Sharing Community for programmer and developer-Open, Learning and Share
Click Here to Ask a Question

...